Family planning in context: sensitivity of fertility desires and intentions to ecological cues - Adair, Lora E. (Kansas State University, 2015)
Although fertility decision-making has been the source of considerable theoretical and empirical investigation, the effect of several contextual variables on individuals’ fertility decision-making processes are not yet understood. For example, are individuals more strongly influenced by social forces that are informational or normative? Also, do individuals change their fertility intentions based on their current and developmental economic conditions? Further, how ‘shared’ are reproductive decisions within a couple, are males or females more likely to get what they want? This 3-study program of research used both experimental and exploratory qualitative methods to elucidate the nature of these unresolved issues within the domain of fertility decision-making. Study 1 (N = 344, M[subscript]age = 23, SD[subscript]age =6.41, 59.3% female) found that highly motivated individuals’ fertility intentions were more susceptible to informational, compared to normative messages (the opposite was true for unmotivated participants). Study 2 (N = 249, M[subscript]age = 24, SD[subscript]age =6.10, 61.4% female) found that exposure to mortality primes up-regulated fertility intentions for individuals with “fast” life history strategies, but facilitated the down-regulation of fertility intentions for individuals with “slow” life history strategies. Interestingly, resource scarcity primes were associated with the postponement of fertility plans in individuals’ with “fast” life history strategies. Study 3 (N = 120, M[subscript]age = 21, SD[subscript]age =4.96, 50% female) found that, contrary to predictions, the similarity of couples’ gender role attitudes, career-orientations, and education levels did not significantly predict the frequency of their use of statements coded as compromise and agreement or persuasion and disagreement in their discussions regarding their future reproductive plans. Findings do suggest that individuals with higher levels of education were more likely to use persuasion and disagreement statements in their child timing and number discussions with their romantic partner, indicative of greater decision-making power in that particular social exchange. Further, men and women in study 3 were equally likely to use statements coded as compromise and agreement, persuasion and disagreement, and concession when discussing both their future fertility plans as well as their future financial plans.
Keywords: fertility decision-making; life history strategy; intimate couples; power; social influence; Evolution and Development (0412); Psychology (0621); Social Psychology (0451)